A wall of despair: The interplay of the Turkish wall and foreign policy in Syria - SEVER, AYŞEGÜL (My University, 2023)
The wall constructed along the Turkish-Syrian border is one of the new wave of border barriers built in the twenty-first century and represents a radical shift in Turkey’s Middle East policy. The decision to erect the “Turkish Wall” was the result of President Recep Tayyip Erdoğan’s government’s desire to improve relations with the European Union, Russia, and the United States in the context of the Syrian Civil War. This article uses the concept of “fortified boundaries” as its framework to analyze the transformed border.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC)